Stability of Delayed Markovian Switching Stochastic Neutral-Type Reaction-Diffusion Neural Networks (Journal of Nonlinear Modeling and Analysis, 2024)
This paper is concerned about exponential stability in mean squareof Markovian switching delayed reaction-diffusion neutral-type stochastic neural networks (RNSNNs). By Lyapunov function method, several novel stabilitycriteria on exponential mean square stability of Markovian switching RNSNNswith time-varying delays are obtained. In the end, two examples are given toverify the feasibility of our findings.